2021
DOI: 10.1001/jamahealthforum.2021.2324
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cost Sharing With Delayed and Complicated Presentation of Acute Appendicitis or Diverticulitis

Abstract: IMPORTANCE Treatment delays are associated with increased morbidity and cost of disease, although the extent to which cost sharing influences timely presentation and management of acute surgical disease remains unknown. Given recent policy changes using cost sharing to modify health care behavior, this study examines the association of cost sharing with the health of the patient at presentation and with receipt of optimal or minimally invasive surgery.OBJECTIVE To assess whether cost sharing is associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…However, patients in each high-deductible tier had greater odds of complications than those who were enrolled in traditional plans, indicating that primary results were not skewed by patients enrolled in catastrophic deductible plans. The modest but statistically significant effect size is supported by what is to our knowledge the only other current publication to examine HDHP and urgent surgical conditions (diverticulitis and appendicitis) …”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, patients in each high-deductible tier had greater odds of complications than those who were enrolled in traditional plans, indicating that primary results were not skewed by patients enrolled in catastrophic deductible plans. The modest but statistically significant effect size is supported by what is to our knowledge the only other current publication to examine HDHP and urgent surgical conditions (diverticulitis and appendicitis) …”
Section: Discussionmentioning
confidence: 57%
“…When considering the vast numbers of these operations annually, the costs quickly become substantial. While the findings do not provide direct evidence that these results are solely owing to delay in seeking care, HDHPs have been associated with delay in care and decreased health care use in other clinical contexts . To better understand the effect of cost sharing on patients undergoing surgery, it would be prudent to examine whether these patterns are consistent across other general surgery conditions in which cost-related delay in care has an effect on patient outcomes.…”
Section: Discussionmentioning
confidence: 86%
“…The findings by Loehrer and colleagues also add important nuance to our understanding of the association between insurance coverage and clinical disease complexity at presentation. Analyses of the Affordable Care Act’s expansion of Medicaid eligibility have repeatedly shown that decreases in the uninsured rate were associated with more timely presentation across a variety of diseases ranging from earlier stage of cancer presentation to less complex presentation for emergency surgical and acute vascular conditions .…”
mentioning
confidence: 85%
“…The finding by Loehrer and colleagues of a significant association between cost sharing and patient presentation for emergency surgical conditions suggests that cost sharing is not only hazardous to patients’ clinical health but also to their financial well-being. Specifically, their findings show that individuals with higher cost sharing were more likely to present with more complex acute surgical disease than those with lower cost sharing.…”
mentioning
confidence: 99%
See 1 more Smart Citation